Penerapan Pendidikan Matematika Realistik untuk Meningkatkan Kemampuan Memecahkan Masalah Matematika SD/MI - Amalia Soleha; Deswita Khofipah Saputri; Lena Saputri; Djuita Hidayati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Realistic Mathematics Education (RME) is an approach to teaching mathematics that emphasizes the use of real-world contexts to enhance students' understanding and problem-solving abilities. This study explores the implementation of Realistic Mathematics Education (RME) at SDN 2 Mataram to enhance students' problem-solving skills in mathematics related to real-life contexts. Observations and interviews with teachers indicate that this approach effectively improves students' understanding and motivation. Through steps such as understanding the contextual problem, explaining, solving, comparing answers, and drawing conclusions, students become more active in learning. RME has proven to help students solve mathematical problems using real-world contexts, such as shopping or measuring objects. This approach positively impacts mathematics instruction at the elementary school level.